Stable isotopes are quantitative indicators of trophic niche. (28th August 2019) - Marshall, Harry H.; Inger, Richard; Jackson, Andrew L.; McDonald, Robbie A.; Thompson, Faye J.; Cant, Michael A.
Abstract: Hette‐Tronquart (2019, Ecol. Lett.) raises three concerns about our interpretation of stable isotope data in Sheppard et al . (2018, Ecol. Lett., 21, 665). We feel that these concerns are based on comparisons that are unreasonable or ignore the ecological context from which the data were collected. Stable isotope ratios provide a quantitative indication of, rather than being exactly equivalent to, trophic niche.